2022
DOI: 10.30821/axiom.v10i2.10331
|View full text |Cite
|
Sign up to set email alerts
|

Ethno-Flipped Classroom Model: Sebuah Rekomendasi Model Pembelajaran Matematika Di Masa New Normal

Abstract: <p class="AfiliasiCxSpFirst" align="left"><strong>Abstrak:</strong></p><p class="AfiliasiCxSpMiddle">Pembelajaran matematika jarak jauh berbasis teknologi dapat memberikan dampak positif maupun negatif baik pada siswa maupun guru. Faktor yang memberikan dampak negatif disebabkan oleh pelaksanaan pembelajaran yang tidak memperhatikan <em>personal factor</em> dan <em>personal behavior</em> baik siswa maupun guru. Faktor lainnya adalah pelaksanaan pembelajaran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
1
6
0
3
Order By: Relevance
“…The results of preresearch observations were carried out and showed that there was still passive discussion and a lack of understanding of physics in the learning process. This is in line with Ramadhani et al [13], who explained that front-end analysis is needed to review and describe problems and solutions for research. Learner analysis: the initial diagnostic analysis results showed that five students, or 45%, had a kinesthetic learning style, five students, or 45%, had an audio-visual learning style, and one student, or 9%, did not conduct an initial diagnostic test with a statement of absence.…”
Section: Resultssupporting
confidence: 82%
“…The results of preresearch observations were carried out and showed that there was still passive discussion and a lack of understanding of physics in the learning process. This is in line with Ramadhani et al [13], who explained that front-end analysis is needed to review and describe problems and solutions for research. Learner analysis: the initial diagnostic analysis results showed that five students, or 45%, had a kinesthetic learning style, five students, or 45%, had an audio-visual learning style, and one student, or 9%, did not conduct an initial diagnostic test with a statement of absence.…”
Section: Resultssupporting
confidence: 82%
“…The flipped classroom model that can be integrated with the ethnomathematics approach is an interesting learning model innovation and has a significant impact on the development of students' mathematics competencies. Ramadhani, Syahputra, et al (2021) added that the support of constructivist learning theory, self-determination theory, cognitive load theory, and self-regulated theory proves that the integration of the flipped classroom model and the ethnomathematics approach has a real effect on students to be more motivated to be active in learning, increase student confidence and selfefficacy, gain freedom in exploring learning, and the presence of collaboration between students which creates the expected social interaction in learning.…”
Section: Discussionmentioning
confidence: 99%
“…The researcher has conducted a preliminary study by examining the impact of distance learning conducted as a result of the COVID-19 pandemic (Ramadhani, Sihotang, et al, 2021). The researcher conducted an analytical review by reviewing various research results related to the use of technology in the learning process and factors that are not considered in bringing flexibility to technologyintegrated learning (Ramadhani, Syahputra, et al, 2021). The review of the analysis conducted by the researcher also refers to the importance of paying attention to technology adaptation factors, students' mental readiness, and self-habits related to the implementation of learning that brings flexibility through technology integration.…”
Section: Methodsmentioning
confidence: 99%
“…One innovation that can be implemented is the use of digital technology to explore and embrace diverse mathematical practices in various cultures. By utilizing digital platforms, students can learn traditional mathematical practices from various cultures, such as problemsolving, measurement, or number order, which can enrich their understanding of mathematical concepts (Suherman & Vidákovich, 2022); (Ramadhani et al, 2021). In addition, technology can also be used to facilitate collaboration between students from different cultural backgrounds in solving mathematical problems related to their cultural heritage (Yolanda Br Tarigan & Syahputra, 2023).…”
Section: Mathematics Learning Innovation With Ethnomathematicsmentioning
confidence: 99%